Comparative proteomic analysis of oil palm (Elaeis guineensis Jacq.) during early fruit development - Kok, Sau Yee; Namasivayam, Parameswari; Ee, Gwendoline Cheng Lian; Ong Abdullah, Meilina (Elsevier, 2021)
To gain insights on protein changes in fruit setting and growth in oil palm, a comparative proteomic approach was undertaken to study proteome changes during its early development. The variations in the proteome at five early developmental stages were investigated via a gel-based proteomic technique. A total of 129 variant proteins were determined using mass spectrometric analysis, resulting in 80 identifications. The majority of the identified protein species were classified as energy and metabolism, stress response/defence and cell structure during early oil palm development representing potential candidates for the control of final fruit size and composition. Seven prominent protein species were then characterised using real-time polymerase chain reaction to validate the mRNA expression against the protein abundant profiles. Transcript and protein profiles were parallel across the developmental stages, but divergent expression was observed in one protein spot, indicative of possible post-transcriptional events. Our results revealed protein changes in early oil palm fruit development provide valuable information in the understanding of fruit growth and metabolism during early stages that may contribute towards improving agronomic traits.